Reimagining Education – Exploring the Factors Influencing Perception Towards Artificial Intelligence and Its Educational Outcome - Amrita Rajkumar Harjani (Journal of Informatics Education and Research, 2024)
In recent years, there has been a growing interest in exploring the integration of AI technologies into educational settings to enhance teaching and learning experiences. However, the successful adoption of AI in education depends significantly on the perceptions and attitudes of teachers, who play a crucial role in implementing and utilizing these technologies in the classroom. The article aims to examine teachers’ perceptions of using artificial intelligence in education, exploring their attitudes, concerns, and expectations regarding AI integration. In addition, many school administrators and educators have not had direct experience with AI-based learning assistance and may just see it as a marginally improved kind of instructional technology. The researcher concluded that, educators should try out AI-powered learning tools for themselves to get a feel for how they may enhance STEM education—and scientific writing in particular—before implementing them in the classroom and assessing their efficacy. Understanding the relationship between AI integration and educational outcomes is essential for informing policy, guiding practice, and fostering evidence-based approaches to AI implementation in education. Many educators feel ill-equipped to navigate the complexities of AI technologies leverage them effectively in the classroom. Educators, policymakers, and technology developers must work collaboratively to establish robust data protection policies, transparent data governance frameworks, and mechanisms for ensuring algorithmic fairness and accountability.